بناء العتبة العنوانية في الأعمال الشعرية لـ "محمد جربوعة - أقطي,حاتم; طويل,سعاد (University of Eloued جامعة الوادي, 2023)
تهدف الدراسة إلى الكشف عن التشكيل التركيبي والدلالي للعتبات العنوانية في الأعمال الشعرية لصاحبها محمد جربوعة. أُعتمد منهج تحليلي لخمسة دواوين شعرية. جاء البناء التركيبي لمعظم العناوين جمل اسمية متحررة في دلالاتها أبانت أحوال متعددة لذات سوية مسلمة بالفطرة، معتزة بدينها، متحسرة على وضع أمتها، تعيش المجهول وتعانق الحقيقة، متقلبة في أحاسيسها...، فأبدع الشاعر في وصفها معتمدا تشكيلا بصريا غاية في الدقة والإبهام. Abstract: The study aimed to discover the structural and semantic construction of the title thresholds in the poetic works of Mohammed Jarboua. It based analytical approach, where it was taken five Poetry collections. The structural construction of most titles was nominal sentences, that are liberal in their connotations, it demonstrated multiple conditions for the normal self, Muslim instinctive, proud of its religion, bemoans the circumstance of its nation, live in the unknown and embrace the truth, fickle in its feelings..., so the poet excelled in describing it through visually formed extremely accurate and vagueness.
Keywords: عتبة عنوانية; تشكيل بصري; بناء تركيبي; سيمياء; Title Threshold; Visual Formation; Structural Construction; Semiotic